Reliving the debate concerning nursing education: from where we departed and to where we are going - Jouhanna do Carmo Menegaz; Daiana Kloh; Hilário Mattioli Neto; Jussara Gue Martini; Flávia Regina de Souza Ramos; Vânia Marlil Schubert Backes (Universidad de Antioquia, 2013)
Objective. To identify the perception of both students and professors from a graduate nursing program in the South of Brazil concerning the historical process of nursing education in the country. Methodology. Qualitative, exploratory-descriptive study. Data were collected from professors using semi-structured interviews and focus groups with 12 students, analyzed using Minayo's operational proposal. The following categories emerged: 'from where we departed'; 'transition process'; and 'to where we are going'. Results. The participants showed knowledge concerning the process that permeates the education of Brazilian nurses from the establishment of the first school and determination of national curricular guidelines, highlighting challenges and future prospects. Conclusion. There is advancement toward the reorientation of educating more critical, creative nurses aligned with the demands of the Brazilian Unified Health System.